Judicialização no Supremo Tribunal Federal: a seletividade positiva nas reclamações constitucionais. - Pontes, Juliana de Brito Giovanetti (2020)
The exponential rise in the number of disputes that annually reach the Brazilian Supreme Court produces a natural consequence: selectivity. The Supreme Court Justices select the issues that will be considered by the court and sometimes they select - expressly or tacitly - those issues that will not be considered. Positive selectivity by the judges is represented by the cases that are brought to trial. Conversely, negative selectivity is represented by cases that are not brought to trial. Although the influence of the Supreme Court in Brazil’s legal and political spheres is recognized, knowledge about its decision-making process is still significantly limited, as is understanding of any personal biases of the decision-making justices. Therefore, in order to understand positive selectivity as it relates to judicial reviews, especially regarding the judgments of constitutional complaints (a legal-procedural instrument aimed at preserving jurisdiction and guaranteeing the authority of the Brazilian Supreme Court), the object of this thesis is the analysis of the actual circumstances that, in those complaints, may increase or decrease the chances of a favorable judgment. Thus, through binary logistic regression, also known as logit, we seek to analyze what these circumstances would be. The combination of testable variables, based on the strategic and legalistic causal models, allows the identification of which factors would influence judicial decisions in constitutional complaints, and this study aims to understand the decision dynamics of the Brazilian Supreme Court. A sample of 379 cases, randomly drawn and proportionally distributed over the period 1988 to 2017, was analyzed. The variables used to test the model were extracted and coded by binary logistic regression. This research does not intend to create a jurimetry tool, but rather to contribute, within its specific scope, to the understanding of the strategic relationships between the various branches of the Brazilian state and to expand our knowledge about the effects of judicial reviews arising from the use of constitutional complaints.